Investigation of the estuarine salinity-morphology characteristics effects - Nurul Shafiqah, Shahrulnizam; Nuryazmeen, Farhan Haron; Siti Nurhayati, Mohd Ali; Noor Suraya, Romali; Ibrahim, Saerahany Legori; Sediqi, Mohammad Naser; Mazlin, Jumain; Zulkiflee, Ibrahim (Penerbit Akademia Baru, 2024)
Estuaries, where freshwater rivers meet ocean saltwater, are vital coastal ecosystems characterized by water layer stratification. Human activities, including dredging, industrial waste disposal and coastal development, disrupt estuarine dynamics, leading to altered salinity levels and ecological threats. Sudden salinity changes, often driven by these activities, jeopardize estuarine species adapted to specific salinity conditions, potentially causing biodiversity decline and ecosystem collapse. This research focuses on two cases: Case 1 examines an unaltered estuary, replicating natural conditions, while Case 2 introduces a constriction pattern mimicking real-world estuaries influenced by geological or human-made features. Systematic salinity monitoring along multiple stations, including longitudinal, transverse and vertical directions, reveals a significant correlation between estuary shape and salinity distribution. In Case 2, a central constriction substantially impacts saltwater and freshwater mixing time, resulting in downstream salinity variations. These findings have broader implications, informing environmental conservation, climate adaptation, resource management and infrastructure design. Additionally, they advance fluid dynamics and environmental science, potentially fostering innovation across disciplines. In summary, this research offers practical solutions for the preservation and sustainable development of estuarine ecosystems.